Fluke-Related Cholangiocarcinoma: Challenges and Opportunities - J. Luis Espinoza (Pathogens, 2023)
Cholangiocarcinoma encompasses a heterogeneous group of highly aggressive malignancies, arising from the biliary tract, that are often associated with poor survival rates [...]